2017
DOI: 10.1017/iop.2017.19
|View full text |Cite
|
Sign up to set email alerts
|

In Defense of Responsible Survey Key Driver Analysis

Abstract: In their focal article, Cucina, Walmsley, Gast, Martin, and Curtin (2017) raise a number of concerns about survey key driver analysis (SKDA). Although many are valid, we think their critique ultimately goes too far and risks throwing the baby out with the bathwater. We have found that SKDA can be an effective way to generate insight and action when analysis is done correctly and results are used appropriately. In this response article, we first provide data that counters Cucina et al.’s findings. Then we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…More specifically, the identified key drivers are most highly associated with the outcome (oftentimes employee engagement). Cucina et al (2017) called for the moratorium of this practice, which evoked a series of commentaries (see Hyland et al, 2017 ; Johnson, 2017 ; Klein et al, 2017 ; Macey and Daum, 2017 ; Rotolo et al, 2017 ; Scherbaum et al, 2017 ). Similarly, some authors have suggested that managers do not need statistical training to recognize significant differences, but instead can deal best with their data by examining percentages of favorable and unfavorable results and comparing them to other departments or past survey results ( Dodd and Pesci, 1977 ).…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, the identified key drivers are most highly associated with the outcome (oftentimes employee engagement). Cucina et al (2017) called for the moratorium of this practice, which evoked a series of commentaries (see Hyland et al, 2017 ; Johnson, 2017 ; Klein et al, 2017 ; Macey and Daum, 2017 ; Rotolo et al, 2017 ; Scherbaum et al, 2017 ). Similarly, some authors have suggested that managers do not need statistical training to recognize significant differences, but instead can deal best with their data by examining percentages of favorable and unfavorable results and comparing them to other departments or past survey results ( Dodd and Pesci, 1977 ).…”
Section: Resultsmentioning
confidence: 99%